TESTING THE ACTIVITY AND FORMULATION OF NATURAL HAND SOAP BASED ON NATURAL SURFACTANTS OF LERAK FRUIT (Sapindus rarak DC.) AGAINST Staphylococcus aureus - Rose Intan Perma Sari; Natasha Ardinata; Oky Hermansyah; Suci Rahmawati; Camelia Dwi Putri Masrijal (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Lerak (Sapindus rarak DC.) is a fruit belonging to the Sapindaceae family that usually grows in tropical forests. Lerak fruit flesh contains the main active compound, saponin. Saponin is a natural surfactant with foaming and emulsifying properties. The use of synthetic surfactants in the manufacture of hand soap sold on the market can have negative impacts, such as irritation and denaturation of proteins in the outer epidermis layer in humans if exposed too often. This study aimed to determine whether lerak can be formulated into natural hand soap as a natural surfactant and determine its antibacterial activity against Staphylococcus aureus bacteria. Lerak fruit solutions were prepared using a maceration method. The resulting solution was then formulated into hand soap at concentrations of 10%, 30%, and 50%. The evaluation of the natural hand soap preparation from the lerak fruit included organoleptic evaluation, homogeneity, pH, viscosity, foam height, and antibacterial activity against Staphylococcus aureus bacteria using the disc diffusion method. Based on the research results, Lerak Fruit (Sapindus rarak DC.) can be formulated as a natural surfactant in hand soap at concentrations of 0%, 10%, 30%, and 50%. Based on the evaluation of the physical properties in the foam height test, F1, F2, and F3 met the requirements, whereas F0 did not meet the requirements in the foam stability test because it did not contain lerak fruit extract, so no foam formed ...